Achieving High‐Quality Freshwater from a Self‐Sustainable Integrated Solar Redox‐Flow Desalination Device. Issue 30 (23rd June 2021) - Ramalingam, Karthick; Wei, Qiang; Chen, Fuming; Shen, Kaixiang; Liang, Mengjun; Dai, Jinhong; Hou, Xianhua; Ru, Qiang; Babu, Ganguli; He, Qinyu; Ajayan, Pulickel M.
Abstract: Solar‐assisted electrochemical desalination has offered a new energy–water nexus technology for sustainable development in recent studies. However, only a few reports have demonstrated insufficient photocurrent, a low salt removal rate, and poor stability. In this study, a high‐quality freshwater level of 5–10 ppm (from an initial feed of 10 000 ppm), an enhanced salt removal rate (217.8 µg cm −2 min −1 of NaCl), and improved cycling and long‐term stability are achieved by integrating dye‐sensitized solar cells (DSSCs) and redox‐flow desalination (RFD) under light irradiation without additional electrical energy consumption. The DSSC redox electrolyte (I − /I3 − ) is circulated between the photoanode (N719/TiO2 ) and intermediate electrode (graphite paper). Two DSSCs in parallel or series connections are directly coupled to the RFD device. Overall, this hybrid system can be used to boost photo electrochemical desalination technology. The energy–water nexus technology will open a new route for dual‐role devices with photodesalination functions without energy consumption and solar‐to‐electricity generation. Abstract : Flow‐based dye‐sensitized solar cell is directly integrated with redox‐flow desalination device to achieve high performance of photo‐desalination. A high‐quality water product of 5 ppm is obtained from the initial salt feed concentration of 10 000 ppm. The salt removal rate is up to 209.7 µg cm −2 min −1 .